Orbital metastasis of squamous cell cervical cancer: A case report and review of literature - Mendia, Ana (Gynecol Oncol Rep, 2020)
Common sites of metastatic disease seen in cervical cancer most often include the lungs and liver. Orbital metastasis secondary to cervical carcinoma is a rare form of metastatic disease. We report a 73-year-old woman who presented with ocular symptoms found to be secondary to orbital metastasis of cervical cancer. She underwent palliative radiation to the orbit and pelvis followed by systemic chemotherapy with carboplatin, paclitaxel, and bevacizumab. Prompt intervention was able to salvage her vision and improve her quality of life significantly. We identified 5 similar reported cases in which orbital metastasis was diagnosed simultaneously at the time of cervical cancer diagnosis. In these five cases, patients were treated with a combination of radiation and chemotherapy. Our case demonstrates an unusual presentation of isolated orbital metastatic disease secondary to squamous cell carcinoma of the cervix. Physicians should be aware that cervical cancer may metastasize to the eye leading to vision loss, and prompt intervention may be able to salvage one’s vision and improve quality of life.